Historical transcendence and the reality of God: a christological critique - Anderson, Ray Sherman (The University of Edinburgh, 1973)
This thesis maintains that the reality of God can be known as an act of divine self-transcendence, with one pole of that self-transcendence considered to be an act from the side of the creature toward the Creator by the Son of God. Thus, the 'historical transcendence' of God is an 'intra-divine' act which takes place in absolute solidarity with man through the life and person of the Incarnate Logos—Jesus Christ. The 'inner logic' of historical transcendence exposes itself to us through the Incarnation as the rationale which unites Creator and creation in a unity of relation, a rationale possessing a real epistemic content in the form of a problematic. The reality of God is held to be problematical to any abstraction from participation in that act of historical transcendence. This participation, called 'lived transcendence', unites the Word and Spirit of God in one action of faith, by which creaturely existence is given its completion in the life of God, which is its eschaton.

The thesis takes up, first of all, the crisis of the reality of God in the form of a 'crisis of transcendence.' This crisis is radicalized in order to expose the reality of God as totally 'other' to all creaturely existence. In doing this, the language of transcendence and immanence, in its traditional form, is shown to be inadequate to express the correlation between a created reality and a reality totally 'other' to it. For the purpose of this thesis, transcendence is now conceived to be the action of the Other concretizing himself in relation. Because this relation is problematical when one abstracts from the Other (i.e., from action into reflection), the action of the Other in relation (transcending his own immanent existence) is at the same time the transcendence of the Other (his freedom) and his bond with the reality of concrete existence. In this way, transcendence, and not immanence, is taken to be the bond between the concrete and the absolute. With this metaphysical framework assumed as an axiological point of departure, the Incarnation is then explored with the intent of laying bare the intrinsic structure of divine transcendence as the act and the action of the Creator in relation with his creation.

In the relation of God to Israel, the 'inner logic' of Incarnation is shown to point us, on the one hand, back to the covenant of creation with its covenant response grounded in the transcendence of God as Creator, and, on the other hand, forward to the Incarnation itself, in which the eternal Logos completes the covenant response from the furthest side of human estrangement. The Incarnation can now be known as the historical transcendence of God because it is God's act of utter solidarity with the world through the assumption of a complete humanity, while at the same time, it is the act of the Son of God toward the Father and the Father toward the Son within the perfect unity of divine love. The transcendence of God can thus be said to 'originate' an historical act of God in a non-mythological sense. What we call kenosis, because it appears as an act of utter condescension and even humiliation on the part of the Son of God, is actually revealed to be the depth of divine transcendence experienced as an intra-divine relation into which man is taken with his full humanity. Historical transcendence, then, is God, as 'totally Other', in relationship with himself through the solidarity of the Logos with humanity in the life of the Spirit. This utter solidarity of God with man is also the absolute 'difference' between God and man (because the solidarity is an act of transcendence), and it is this 'difference' which makes possible a real and rational relation. For the rationality is given as an intrinsic reality of the relation through the transcendence of God.

The argument of the thesis turns on the hinge of historical transcendence and swings forward into the life of lived transcendence. The reality of God places man between the 'two poles of divine transcendence.' The life of the Spirit, as one pole of transcendence, relates man to God through the Spirit's own unity with the Father and the Son. However, the transcendent ground for the reality of Spirit is the historical life of the Incarnate Word—Jesus Christ. The Scripture, as the 'pole' of historical transcendence which testifies to man's place in the life of God through a common humanity with the Incarnate Son, becomes the channel through which the Spirit reaches to ground faith in the rationale of historical transcendence. Historical transcendence, then, creates the 'kenotic' bond of community between man and God; lived transcendence, through the power of the Spirit, creates the 'ek-static' bond of communion between creaturely existence and the life of the triune God.

The 'kenotic community' and the 'ek-static community', as a schematized way of tracing out the inner logic of the Incarnation, suggest, finally, the ways in which the transcendence (and, therefore, the reality) of God can be located in concrete 'thresholds' of historical existence, in such a way that God, as the eschaton of creation, gives each penultimate moment ultimate significance.